Proces wejścia w życie amerykańskiego Jednolitego Kodeksu Handlowego - Niemotko, Waldemar (Wydział Prawa i Administracji UAM, 1969)
The incessant growth of the US foreign trade and development of its modern technical facilities, did not find any pendant in the traditional legal regulation of the matter. The reason was the federal system leading to diversity of legislatures according to the constitutional rights exercised by each of 50 states and Puerto Rico, and accordingly by Congress of the United States in relation to the District of Columbia and the federal territories. „Splendid isolation" has left essential disadvantages as regards commerce itself (in the broad meaning of this word as adopted by Anglo-American legal system). Disregarding the Incoterms 1936, the Revised American Foreign Trade Definitions have been introduced in 1941. Only few international conventions are in force in the United States. The convention on checks, convention on bills of exchange, many maritime conventions, and even done in New York City convention on recognition and enforcement of foreign arbitral awards, have not yet been adopted in this country. Signature being ever put on any act of this kind does not secure the prosperous perspectives as regards its adoption by particular states. In order to avoid disadvantages of the legal situation as described above, being improper for promoting of the interstate commerce relations too, a series of uniform acts has been duly adopted by legislatives of particular states. The Uniform Commercial Code, being an advanced stage of the unification efforts, is — in the opinion of Professor Soia Mentschikoff — the most ambitious Codification ever undertaken in the Anglo - American legal world. After testing of its draft in series of discussions, the 1952 Official Text and Comments Edition has been produced as a private proposal for state legislatives. Since 1954 (Pennsylvania) the code has been adopted by every state except Louisiana. In the meantime the deep-seated adherence to the „judge-made law" system was to be surmounted. The main negative aspect of the above system of coming the code in force of the will of state legislatives, were various local amendements introduced to the text. Therefore, a full unification by one federal act is now urgently needed.
Entry into Force of the United States Uniform Commercial Code